Influência das condições ambientais e técnicas de produção sobre a incidêcia de enfermidades no cultivo de camarão marinho, Litopenaeus vannamei, no estado do Ceará - Martins, Pedro Carlos Cunha (2003)
This study investigated the influence of environmental conditions and grow-out management practices on the occurrence of diseases during farming of the penaeid shrimp Litopenaeus vannamei. The work was conducted in commercial grow-out ponds located adjacent to two estuaries in the Eastern coast of the State of Ceará, Brazil. One semi-intensive production cycle was monitored throughout the dry season. In the wet season of 2002, three production cycles (two semi-intensive and one super-intensive) were studied. Environmental conditions and management techniques adopted were characterized through tabular and descriptive analyses. Microbiological conditions in the sediment and water of the farmed and natural ecosystems, as well as in cultured shrimp were studied through standard plate counting using PCA and TCBS media. Presumptive bacterial colonies of the genus Vibriowere isolated and identified. A general evaluation of shrimp health status was conducted through wet mounting and histopathology of shrimp organs. Final shrimp grow-out data indicated management practices and environmental conditions positively influenced the balance between the two ecosystems. The type of rearing system used did not influence the number of bacterial present in each ecosystem and in farmed shrimp. Also, the incidence of bacterial and (or)virus lesions in shrimp was not related to the level of intensification. Changes in shrimp health conditions as observed by wet mount analysis were in most cases related to farming conditions. This confirmed management techniques are also appropriate to the preventive sanitary management in shrimp farming. According to the results obtained in commercial ponds, it was concluded the occurrence of diseases is not related to the type of rearing system adopted by the shrimp aquaculture operation. However management practices and environmental conditions, reflected in the adoption of best management practices in each grow-out cycle, are vital to the health status of each pond's ecosystem.